2017
DOI: 10.3389/fcvm.2017.00053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Genetic Risk Score for Coronary Artery Disease on Reducing Cardiovascular Risk: A Pilot Randomized Controlled Study

Abstract: PurposeWe tested whether providing a genetic risk score (GRS) for coronary artery disease (CAD) would serve as a motivator to improve adherence to risk-reducing strategies.MethodsWe randomized 94 participants with at least moderate risk of CAD to receive standard-of-care with (N = 49) or without (N = 45) their GRS at a subsequent 3-month follow-up visit. Our primary outcome was change in low density lipoprotein cholesterol (LDL-C) between the 3- and 6-month follow-up visits (ΔLDL-C). Secondary outcomes include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…While there remains an additional cost for genetic scores, albeit modest, it is reasonable to require an outcome benefit to be demonstrated before arguing for adding to medical expenditure. In a small pilot randomized controlled study, we showed the feasibility of delivery of a genetic risk score in a clinical environment [ 35 37 ]. While we did not demonstrate that the score led to an improvement in patient adherence to guideline-based therapeutic advice, others have shown that the incorporation of a genetic risk score into clinical care may increase statin usage (mostly through increased statin prescriptions) [ 38 ].…”
Section: Summary Pointsmentioning
confidence: 99%
“…While there remains an additional cost for genetic scores, albeit modest, it is reasonable to require an outcome benefit to be demonstrated before arguing for adding to medical expenditure. In a small pilot randomized controlled study, we showed the feasibility of delivery of a genetic risk score in a clinical environment [ 35 37 ]. While we did not demonstrate that the score led to an improvement in patient adherence to guideline-based therapeutic advice, others have shown that the incorporation of a genetic risk score into clinical care may increase statin usage (mostly through increased statin prescriptions) [ 38 ].…”
Section: Summary Pointsmentioning
confidence: 99%
“…A review of 18 trials in which people were informed of their genetic risk of various diseases showed no effects on smoking, diet, physical activity, alcohol use, or participation in screening and behavioural support programmes 36. More recent trials using polygenic risk scores to identify those at higher risk of developing diabetes or cardiovascular disease have not fared much better 3738. The premise that having more genetic information motivates people to alter risky behaviours remains unproven 39…”
Section: Clinical Utility Of Predictive Genetic Testingmentioning
confidence: 99%
“…Although the MI-GENES study could not differentiate between effect on the patient versus effect on the health care provider, a more recent study by Knowles et al. (39) looked at the usefulness of GRS as a motivational tool for reducing CAD risk factors. Patients who received standard-of-care plus GRS showed no significant changes, including medication use, blood pressure, physical activity, weight, and high-density lipoprotein concentration compared with standard-of-care patients (39) .…”
Section: Spotlight On Precision Medicine In a Common Cvd: Cad And Carmentioning
confidence: 99%